Helicascus gallicus sp. nov., a new freshwater pleosporalean ascomycete from France - Zhang, Ying; Yang, Yanjiao; Zhang, Xiaodong; Cui, Baokai; He, Shuanghui; Fournier, Jacques (Phytotaxa, 2014)
x A new species of Helicascus (H. gallicus) is described and illustrated from submerged wood collected from aquatic habitats in western and southern France. It is morphologically characterized by multilocular ascomata covered by a thick clypeus and sharing a common ostiole, clavate asci with endoascus coiling in the pedicel, cellular pseudoparaphyses, and brown 2-celled ascospores with a marked submedian septum. Its relationships with other species of Helicascus are discussed based on morphology and 28S and ITS nrDNA sequence comparisons.